1993
DOI: 10.1007/bf01207735
|View full text |Cite
|
Sign up to set email alerts
|

Follicle stimulating hormone levels on cycle day 3 predict ovulation stimulation response

Abstract: Cycle day 3 FSH levels are predictive of the ovulation response and probability of pregnancy in stimulated cycles and can be of value in patient selection and counseling in IVF and GIFT programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Serum FSH levels rise to compensate for a diminished ovarian response to stimulation. Since Scott and colleagues 4 reported the predictive value of day-3 serum FSH levels for IVF outcome, several studies have been performed to determine the importance of day-3 FSH concentration [5][6][7][8][9] . The threshold values as demonstrated by the number of mature oocytes collected have varied between 10.8 and 25.0 mIU/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum FSH levels rise to compensate for a diminished ovarian response to stimulation. Since Scott and colleagues 4 reported the predictive value of day-3 serum FSH levels for IVF outcome, several studies have been performed to determine the importance of day-3 FSH concentration [5][6][7][8][9] . The threshold values as demonstrated by the number of mature oocytes collected have varied between 10.8 and 25.0 mIU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding FSH concentration, previous studies have utilized the value in the early follicular phase of the natural cycle [4][5][6][7][8][9] . However, there has also been a report of a practical method for determination of FSH in the IVF cycle induced by GnRH agonist suppression 14 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been controversies concerning the cutoff value of basal serum FSH level that could represent the ovarian response according to the laboratories and the assay technique used. 21,22) In this study, we used the concentration of 8.5 mIU/ ml as the cutoff value of ovarian response by our results of the previous study.R) However, there is also intercycle variability of basal serum FSH22,23) and the single measurement of basal serum FSH is not seemed to be accurate for prediction of ovarian response. It was reported that the patients with low basal serum FSH level had also minimal intercycle variation of FSH level than those with high basal serum FSH however, it is possible that the patients with low basal serum FSH level at the measurement have actually high basal serum FSH level at commencement of COH.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian responsiveness has previously been shown to be related to FSH levels early in the same cycle without pituitary desensitisation (Toner et al 1991; Ebrahim et al 1993). We have shown that this association holds when FSH is measured in an earlier cycle, which should be of greater practical predictive value.…”
Section: Discussionmentioning
confidence: 99%